Manganese Oxide as an Inorganic Catalyst for the Oxygen Evolution Reaction Studied by X‐Ray Photoelectron and Operando Raman Spectroscopy. Issue 4 (16th December 2020) - Radinger, Hannes; Connor, Paula; Stark, Robert; Jaegermann, Wolfram; Kaiser, Bernhard
Abstract: Manganese oxide (MnOx ) is considered a promising material for the oxygen evolution reaction (OER) to replace noble metal catalysts in water splitting. The improvement of MnOx requires mechanistic and kinetic knowledge of the four‐electron transfer steps of the OER. X‐ray photoelectron spectroscopy, a widely used tool to characterize the electronic structure of thin films, is used in combination with surface‐enhanced Raman spectroscopy to gain a deeper knowledge of the different mixed MnOx types and their respective change in chemical composition. Using Raman spectroscopy during electrochemical measurements, all samples were found to reveal Birnessite‐type MnO2 motifs in alkaline media at an applied potential. Their activity correlates with two shifting Raman active modes, one of them being assigned to the formation of Mn III species, and one to the expansion of layers of MnO6 octahedra. A special activation treatment leads independent of the starting material to a highly amorphous mixed‐valence oxide, which shows the highest OER activity. Abstract : Shifting sands of time : Operando Raman spectroscopy reveals Birnessite‐type MnO2 motifs in alkaline medium at an applied potential independent of the starting material. Their activity correlates with two shifting Raman active modes. A special activation treatment leads to a highly amorphous mixed‐valence oxide, which shows the highest oxygen evolution activity.